2013
DOI: 10.1590/s1679-62252013000100016
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of capture of fish bycatch in the prawn trawling in northeastern Brazil

Abstract: The prawn fishery produces more discards than any other type of catch and captures a large quantity of immature individuals. This research aimed to assess the sustainability of capture of fish bycatch in prawn trawling. Each species was assessed according to two groups of criteria: (1) their relative vulnerability to capture by trawl and mortality due to this fishery (2) recovery capacity of the specie after a possible collapse of the population. Within each group, each species was ranked (1-3), being 1 the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…This further highlights the impact of trawling fisheries on the biodiversity of the Brazilian coast. Trawling is the most common shrimping method used in the region, which impacts most the fauna of sciaenids and haemulids, the families that make up a large part of the fish bycatch taken off the coast of Brazil (see Vianna and Almeida, 2005;Branco et al, 2015;Silva-Júnior et al, 2013Marceniuk et al, 2019). This pressure from shrimp trawling operations, combined with the overfishing of some of the commercially important species may lead to widespread ecological impacts and the decline of stocks.…”
Section: New Species Occurrences From the Northern Coast Of Brazilmentioning
confidence: 99%
“…This further highlights the impact of trawling fisheries on the biodiversity of the Brazilian coast. Trawling is the most common shrimping method used in the region, which impacts most the fauna of sciaenids and haemulids, the families that make up a large part of the fish bycatch taken off the coast of Brazil (see Vianna and Almeida, 2005;Branco et al, 2015;Silva-Júnior et al, 2013Marceniuk et al, 2019). This pressure from shrimp trawling operations, combined with the overfishing of some of the commercially important species may lead to widespread ecological impacts and the decline of stocks.…”
Section: New Species Occurrences From the Northern Coast Of Brazilmentioning
confidence: 99%
“…The high catch of juveniles is characteristic of shrimp trawling. In Pernambuco, near to the study site , Silva Júnior et al (2013) observed that 64% of the individuals caught are below the size of first maturation (L 50 ). The low selectivity of the fishing gear (Branco and Verani, 2006) and in our case the very shallow fishing zone may contribute to high juvenile catches, due to the lower swimming capacity at this stage, when compared to the adult specimens.…”
mentioning
confidence: 97%
“…This activity is focused on shallow waters and has great social-economic importance, since approximately 100,000 persons depend directly or indirectly of this fishery for their living (Santos et al, 2006). Previous studies focusing on the bycatch species in the northeast of Brazil (Silva-Júnior et al, 2013;Eduardo et al, 2019;Lira et al, in press) provided valuable biological and population information of a variety of species. However, many species still lack basic knowledge that is required for management and conservation actions, such as length-weight relationships and size at first gonadal maturity and also indicators of the ecological roles of the fish species, especially those related to the balancing of the marine food web which may influence the composition of this ecosystem (Elliott et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Key species are those that make up the community base and, when absent, result in a substantially different community (Mahon and Smith, 1989). The concept of key species can be applied in this study, where 37.2% of the total catch of individuals was from the family Sciaenidae; the high 9/13 representativeness of this family seems to be a common pattern in the sand-muddy bottom areas of the brazilian coast (Muto et al, 2000;Moraes et al, 2009;Silva Junior et al, 2013;Nóbrega et al, 2019). This predominance is common in other estuaries of the world and is due to the fact that this transition between marine/ euryhaline environments occurred several times throughout the evolutionary history of the family.…”
Section: Discussionmentioning
confidence: 99%